Drug testing in elite athletes - the Israeli perspective. - Epstein, S.; Eliakim, A. (Israel Medical Association Journal, 1999)
BACKGROUND: The use of performance-enhancing drugs by athletes, in particular anabolic steroids, is probably one of the major problems in sports today. During the early 1990s the Israeli Sports Federation and Olympic Committee established the Israeli Sports Anti-Doping Committee. OBJECTIVES: To present a follow-up on tests for use of performance-enhancing drugs among elite Israeli athletes from 1993 until the present. METHODS: Since 1993, 273 drug tests (urine samples) were performed in elite Israeli athletes. These tests were done during major competitions, and at random during the regular training season without prior notice to the athletes. The urine samples were sent for analysis to an official drug laboratory of the Olympic Committee in Cologne, Germany. RESULTS: Since 1993, seven (2.7%) male Israeli elite athletes (5 weight lifters, a javelin thrower, and a sprinter) tested positive for performance-enhancing drugs--all of them for anabolic steroids, and two for diuretics as well. DISCUSSION: These findings suggest that the phenomenon of performance-enhancing drug use by elite athletes has also entered Israeli sports, and probably represent the tip of the iceberg among Israeli sportsmen. Therefore, more drug tests should be performed, especially at random without prior notice and during the regular season. Athletes in the most popular sports such as soccer and basketball should also be tested. The concern over the use of these agents is both medical and ethical. In: Isr Med Assoc J 1999 Oct;1(2):79-82